Changes in semantic fluency across childhood: Normative data from Australian-English speakers. (4th March 2018) - Chami, Sara; Munro, Natalie; Docking, Kimberley; McGregor, Karla; Arciuli, Joanne; Baker, Elise; Heard, Rob
Abstract: Purpose : Verbal fluency tests are often used as part of an assessment battery to investigate children's lexical knowledge as well as executive function skills. To date, however, issues surrounding consistency of measurement cloud comparisons across studies, with the developmental performance of Australian-English speaking children also currently lacking. This study tracked verbal fluency development as measured by two semantic fluency tasks that included coding of fluency, clustering and switching type responses. Method : Participants included 355 typically developing Australian-English speaking children (4–10 years) and 46 young adults. Total fluency was determined by the number of words produced for each category (Animals or Food), minus repetitions and rule violations. Semantic clusters (words generated within a subcategory) were coded while switches between single words or subcategories were differentiated and coded as either hard or cluster switches. Result : Fluency showed consistent improvement over age. Cluster Switches and Hard Switches showed some evidence of a plateau in performance relative to fluency, but in opposite direction. Other measures showed no strong trends over age. Results were similar for both semantic categories. Conclusion : Our results highlight the rich information available within a semantic fluency task and the importance of differentiating hard and cluster switches in paediatric samples.